Life cycle assessment of Indonesian canned crab (Portunus pelagicus). (24th May 2022) - Wiloso, Edi Iswanto; Romli, Muhammad; Nugraha, Bambang Arif; Wiloso, Adisa Ramadhan; Setiawan, Arief Ameir Rahman; Henriksson, Patrik J. G.
Abstract: Indonesia is an archipelagic country with abundant marine wealth that makes it the world's second largest producer of fish after China. While most of Indonesia's capture marine fisheries (80%) are consumed domestically, around 90% of blue swimming crab (BSC) products are exported, mainly in cans. This makes up almost half of all BSC products on the global market, with the United States and the European Union being the main importers. We carried out a life cycle assessment (LCA) of canned BSC products from Indonesia. Our LCA evaluated the production of "one tonne of canned BSC" at market as a functional unit (FU), with a cradle‐to‐market system boundary, encompassing wild capture, preprocessing, processing, and distribution to the port of destination at home and abroad. The processing stage was found to be the highest contributor (hotspot) for most of the impact categories considered, mainly due to the use of tin cans for packaging. Despite producing less by‐catch, BSC caught with traps resulted in around threefold greater global warming impact per FU than those caught using nets. We also concluded that BSC meat produced in Java is environmentally preferable to that from Sumatra, as most of the shells were sold as coproducts. In addition to recycling and substitution of packaging materials, environmental improvements can also be obtained by increasing the number of shell‐processing facilities outside Java. The results of this study can be used by the Indonesian government to develop more sustainable practices to avoid overexploitation of BSC and limit its environmental impacts.